Segmental Mesenteric Thrombosis as the Initial Manifestation of Primary Thrombophilia: Clinical Case - Solís-Reyna, Víctor Hugo; Álvarez-Flores, Luis Rodrigo; Agustín-Martínez, Luis Alejandro; Ucán-Gamboa, Dioney Josimar; Flores Lopez, Alejandro Alberto; Ferrera-Salas, Rilma Del Carmen; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2024)
Introduction: Acute mesenteric ischemia is caused by interruption of the blood supply to the intestine, leading to cell damage, intestinal necrosis, and often death of the patient if untreated. AMI can be occlusive or non-occlusive, with primary etiology defined as mesenteric arterial embolism (50%), mesenteric arterial thrombosis (15-25%) or venous thrombosis (5-15%). Clinical case: A 54-year-old male presented to the emergency room with abdominal pain, vomiting, and hypotension. Important history: Systemic arterial hypertension 2 years after diagnosis, without pharmacological treatment, without other important history upon admission. His Current Condition begins: 24 hours prior to admission, with diffuse abdominal pain, of moderate intensity that partially subsides to the administration of NSAIDs, subsequently he presents fever and general malaise, vomiting of gastro-alimentary content is added and he goes to a rural clinic where he is evaluated and referred to a second level hospital. Exploratory Laparotomy reported the following findings: necrotic area of ​​5 cm that covers the entire circumference located at 20 cm from the Angle of Treitz, Total necrosis of the small intestine that involves approximately 70 cm located at 40 cm of the ileocecal valve. Generalized Peritonitis; Resection and manual anastomosis were performed in two planes, resection of 70 cm of terminal ileum, closure of the ileal stump and terminal ileostomy. He had an adequate post-surgical evolution and was discharged due to improvement. Discussion: Surgical intervention aims to evaluate and remove any unsalvageable intestine, prevent further intestinal infarctions with urgent revascularization, and preserve the small intestine. This often involves a midline laparotomy, which allows direct visualization of the intestine to evaluate blood flow through the mesenteric vessels, observe abnormalities of color or appearance of the intestinal serosa, and monitor peristalsis. Additional techniques such as intravenous fluorescein, Doppler, or intraoperative laser angiography may also be used. used to evaluate perfusion.